Eden - Fox, Candice (Fox, Candice. Archer and Bennett, 2015)
Most homicide detective teams run on trust, loyalty, and the shared desire to put killers behind bars. Frank Bennett's partner, Eden Archer, thrives on darkness and danger. She has a rare talent for catching killers - but her idea of justice has little to do with courtrooms.